The First Wives Club [videorecording (DVD)] - Wilson, Hugh, 1943-2018; Midler, Bette; Hawn, Goldie; Keaton, Diane; Smith, Maggie, 1934-; Hedaya, Dan; Pinchot, Bronson; Harden, Marcia Gay; Garber, Victor; Goldsmith, Olivia (Paramount Pictures, 1998)
Three mid-life Manhattanites have more than a longtime friendship in common. After years of helping their hubbies climb the corporate ladder of success, each has been dumped for a newer, curvier model. The trio is determined to turn their pain into gain. They come up with a cleverly devious plan to hit their exes where it really hurts--in the wallet!